The Influence of Asset Structure, Innovation and Technology, Agency Costs, Company Size, and Company Growth on Leverage - Wili Rahma Putra; Agus Munandar (Jurnal Indonesia Sosial Sains, 2025)
Until now, companies that are included in the LQ45 category are companies that attract large investors. Therefore, the company must have the ability to manage the company's financing sources well and avoid company losses. Therefore, this research aims to empirically understand the impact of asset structure, innovative technology, agency costs, firm size, and firm growth on leverage ratio. LQ45 companies listed on the Indonesia Stock Exchange between 2019 and 2021. This research uses causal benchmarking. The sample of this study is LQ45 member companies listed on the Indonesia Stock Exchange for the 2019-2021 period, using the target sampling method. 11 companies meet the research sample criteria and 33 financial reports. The results showed that asset structure, innovative technology, agency costs, and company size significantly affected the leverage ratio. In contrast, the company growth variable had no significant effect on the leverage ratio.